Expression of Caulobacter dnaA as a function of the cell cycle. - Zweiger, G (1994)
The initiation of DNA replication is under differential control in Caulobacter crescentus. Following cell division, only the chromosome in the progeny stalked cell is able to initiate DNA replication, while the chromosome in the progeny swarmer cell does not replicate until later in the cell cycle. We have isolated the dnaA gene in order to determine whether this essential and ubiquitous replication initiation protein also contributes to differential replication control in C. crescentus. Analysis of the cloned C. crescentus dnaA gene has shown that the deduced amino acid sequence can encode a 486-amino-acid protein that is 37% identical to the DnaA protein of Escherichia coli. The gene is located 2 kb from the origin of replication. Primer extension analysis revealed a single transcript originating from a sigma 70-type promoter. Immunoprecipitation of a DnaA'-beta-lactamase fusion protein showed that although expression occurs throughout the cell cycle, there is a doubling in the rate of expression just prior to the initiation of replication.